2012
DOI: 10.1002/jor.22166
|View full text |Cite
|
Sign up to set email alerts
|

Matrix molecule influence on chondrocyte phenotype and proteoglycan 4 expression by alginate‐embedded zonal chondrocytes and mesenchymal stem cells

Abstract: Articular cartilage resists load and provides frictionless movement at joint surfaces. The tissue is organized into the superficial, middle, deep, and calcified zones throughout its depth, each which serve distinct functions. Proteoglycan 4 (PRG4), found in the superficial zone, is a critical component of the joint's lubricating mechanisms. Maintenance of both the chondrocyte and zonal chondrocyte phenotype remain challenges for in vitro culture and tissue engineering. Here we investigate the expression of PRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 52 publications
(65 reference statements)
3
28
0
Order By: Relevance
“…37 Additionally recent study indicated that ECM, such as CS and HA, added to alginate hydrogel induced lubricin expression. 38 Our findings confirmed that incorporation of these ECMs along with cell-adhesions moieties enhanced lubricin secretion of encapsulated chondrocytes. ECM molecule included hydrogel with cell-adhesive characteristic enhanced lubricin secretion.…”
Section: Discussionsupporting
confidence: 81%
“…37 Additionally recent study indicated that ECM, such as CS and HA, added to alginate hydrogel induced lubricin expression. 38 Our findings confirmed that incorporation of these ECMs along with cell-adhesions moieties enhanced lubricin secretion of encapsulated chondrocytes. ECM molecule included hydrogel with cell-adhesive characteristic enhanced lubricin secretion.…”
Section: Discussionsupporting
confidence: 81%
“…Reports from the literature support that mesechymal progenitor cells express PRG4 during TGF-b-induced chondrogensis, however, the mechanisms and pathways involved in this expression are not clear. 12,26,30 As evidence now supports a population of progenitor cells within the superficial zone, stem cell differentiation may be a normal biological process within this zone, and thus signals derived from it provide favorable signals for chondrogenesis. What is not clear from our data is the source, or identity, of the factors that induce chondrogenesis in the superficial zone coculture groups.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Briefly, cartilage plugs (4 mm diameter, 3-6 mm height) were harvested from the femoral condyles of 20-week-old calves using a Sklar Tru-Punch disposable biopsy punch (Sklar Instruments). The top 10% (0.3-0.6 mm) was taken as the superficial zone, and remaining tissue up was defined as the middle and deep tissue zones.…”
Section: Superficial and Middle/deep Zone Explant Section Isolationmentioning
confidence: 99%
“…HyStem consists of HA, a naturally occurring polysaccharide in cartilage with many prochondrogenic functions [1], which makes it a promising biomaterial for cartilage engineering. Indeed, addition of HA to other biomaterials such as alginate, chitosan and fibrin has been shown to enhance extracellular matrix formation [32]. Depending on the degree of polymerization, HA has been shown to have either inflammatory or anti-inflammatory effects [33].…”
Section: Polyactive™mentioning
confidence: 99%